European business environment : doing business in the EU - Somers, Frans J. L. (Noordhoff Uitgevers Groningen, 2010)
Doing business in Europe is increasingly becoming an everyday reality for many companies, not only large corporations, but also small and medium-sized enterprises. This book offers students a practical introduction to how to create, manage and develop business opportunities in the European Union